Pengaruh E-Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pengguna Aplikasi PLN Mobile Pelanggan - Alkirlanda, Alkhatras Bunga; Suprayitno, Eddi; Nasution, Ismail (Universitas Islam Islam Sumatera Utara, 2023)
By following the times, companies provide electronic services (e-service quality). E-service quality or electronic service can be defined as an interactive service offered by service providers, which aims to strengthen the relationship between consumers and service providers. The quality of service of a company is needed to meet the increasingly diverse needs of society. Therefore, entrepreneurs make new innovations to provide the best quality of service. One company that implements online-based service innovations is the State-Owned Enterprise (BUMN) company PT PLN (Persero). PT PLN created a service model in the form of an application called PLN Mobile to make it easier for customers to meet their information needs and interactions with PLN.This study aims to determine the effect of E-quality of service on customer satisfaction of PLN mobile application users of PT PLN (Persero) ULP Perbaungan customers. The population of this study was 1,151 households of electricity meter users using the Slovin sampling formula, obtained a sample size of 43 samples who had downloaded the PLN mobile application in PlayStore. Then for the analysis technique using multiple linear regression analysis and data processing using SPSS software version 20. Based on the research results, it can be concluded that E-Service Quality (Efficient and reliable service, Fullfilment, Security / trust, Site aesthetics, Responsiveness / contact, Ease of use) simultaneously has a significant influence on Customer Satisfaction.